Valuasi Nilai Ekonomi Agrowisata Bukit Waruwangi Menggunakan Metode Biaya Perjalanan: Economic Valuation of Bukit Waruwangi Agrotourism Using the Travel Cost Method - Ivani Febranadya; Juwarin Pancawati; Nanang Krisdianto (P4W LPPM IPB, 2022)
Bukit Waruwangi Agrotourism is a new tourist destination in Serang Regency, Banten Province that offers the experience of enjoying a farm with grassland surrounded by beautiful hillside views. A good understanding of the visitors perception, contributory factors of the visit demand, as well as the potential value of tourism activities are fundamental in formulating effective farm management policies. This paper used the individual travel cost method to estimates the recreational value of Bukit Waruwangi Agrotourism. In general, visitors have a good perception of the farm. However, parking facilities, road access, and visitor shelters need to be improved. Travel costs, education level, and distance significantly affect the recreational demand. The value of a single farm visit is estimated to be Rp 18,266.00 per person and estimated annually at Rp 2,465,900,000.